E-Commerce and Logistics: An Exploratory Study (Journal of International Studies, 2020)
As more companies adopt e-commerce, there is a need for businesses to understand the implications of the virtual value chain activities. This exploratory study looks at how ecommerce has transformed the logistics industry in Malaysia - more specifically at the downstream activities, which include the distribution and sale of products to customers. It also looks at some issues of concern and also opportunities that this brings to the traditional logistics companies. Review of literature shows that e-commerce has had a positive effect on the logistics industry as a whole in the world. It was also revealed that almost all the Malaysian companies (involved in e-commerce) studied, outsourced their delivery services. Choice of the third party logistics (3PL) provider is crucial. Maintaining a good relationship especially communication between the e-commerce companies and the Logistics Service Provider may be a matter of survival.